Chapter 2 Antiphons - Anderson, Michael Alan (Taylor & Francis, 2022)
This chapter centers on the genre of antiphons, which are concise liturgical melodies that frame the recitation of a psalm or groups of psalms in the offices. It begins by charting their conventional pairing with psalms in the Office of the Virgin and the Office of the Dead. As short texted pieces of monophony with modest musical contour, antiphons have a peculiar way of unfolding in books of hours, led by an incipit at the outset and provided in full after the completion of the psalm. This customary presentation is explained, along with the performative ritual of interweaving the invitatory antiphon with Psalm 94. The chapter brings attention to the role of the well-known Marian antiphons in books of hours, as well as to antiphons in the Hours of the Cross and Hours of the Holy Spirit, which are repeated with great frequency.